Psychological interventions and health: critical connections - Belar,Cynthia D. (2000)
The objective of the study was to discuss critical connections between psychological interventions and health can at various levels: the individual/family, the community/worksite, the health care system, and the general population itself. Psychologists have developed interventions that have positively impacted health in the areas of prevention and health promotion, recovery from illness, management of physical symptoms, stressful medical procedures, adherence and health care systems design. Sites of interventions can range from health care clinics and hospitals to school systems, worksites, communities and public health agencies. As the influence of psychological factors in health becomes more widely appreciated, there will be increasing needs for clinical health psychologists who are appropriately trained to provide these services. The Arden House Conference delegates (1983) outlined education and training for clinical health psychologists that has been accepted to date in the United States. In addition to a broad education in the discipline of psychology, clinical health psychologist need knowledge and skills in a broad core areas.